Fundamental tactical principles of soccer: a comparison of different age groups - Borges, P. H.; Guilherme, J.; Rechenchosky, L.; Arantes da Costa, L. C.; Rinadi, W. (Journal of Human Kinetics, 2017)
The fundamental tactical principles of the game of soccer represent a set of action rules that guide behaviours related to the management of game space. The aim of this study was to compare the performance of fundamental offensive and defensive tactical principles among youth soccer players from 12 to 17 years old. The sample consisted of 3689 tactical actions performed by 48 soccer players in three age categories: under 13 (U-13), under 15 (U-15), and under 17 (U-17). Tactical performance was measured using the System of Tactical Assessment in Soccer (FUT-SAT). The Kruskal Wallis, Mann-Whitney U, Friedman, Wilcoxon, and Cohen`s Kappa tests were used in the study analysis. The results showed that the principles of "offensive coverage" (p = 0.01) and "concentration" (p = 0.04) were performed more frequently by the U-17 players than the U-13 players. The tactical principles "width and length" (p < 0.05) and "defensive unit" (p < 0.05) were executed more frequently by younger soccer players. It can be concluded that the frequency with which fundamental tactical principles are performed varies between the gaming categories, which implies that there is valuation of defensive security and a progressive increase in "offensive coverage" caused by increased confidence and security in offensive actions.